ANALYSIS OF VIOLATING AND FLOUTING MAXIM IN MOVIE: PUSS IN BOOTS (2022) - Fadli, Janji Muhammad Alif; Laila, Malikatul (Prosiding University Research Colloquium, 2024)
This research is about Analysis of Violating and Flouting Maxim in Movie: Puss in Boots (2022). Through this research, the researcher aims to find out the types of Violating and Flouting Maxim and to describe the reasons of the characters which had disobeyed the rule of Maxim of conversation. This research utilizes Grice's theory of conversational maxims as a foundational framework for examining communication dynamics. This study adopts a descriptive qualitative approach to investigate the application and implications of Grice's theory of conversational maxims. The researcher uses conversation in the movie Puss in Boots which consists of utterances including Violating and Flouting maxim as data of this research. The technique of analysis refers to comparison and context interpretation of data towards Grice’s maxims of conversation. The result shows that the highest maxim is Violating maxim, followed respectively by the same result of flouting quality and manner maxim, continued by flouting relevance maxim, and the lowest, flouting quantity maxim